The K0/π- ratio and strangeness supression in v p and Mathematical expression charged current interactions - Jones, G; Kennedy, B; O'Neale, S; Böckmann, K; Gebel, W; Geich-Gimbel, C; Nellen, B; Cooper-Sarkar, A; Grant, A; Klein, H; Morrison, D; Schmid, P; et al. (Springer-Verlag, 1985)
Neutral kaon to negative pion production ratios from vp and Mathematical expression charged current interactions in BEBC are presented and compared with LUND fragmentation model predictions. Good agreement is obtained with a strangeness suppression factor λ=0.203±0.014(stat)±0.010(sys). No evidence is seen for an energy dependence of λ in our kinematic region. © 1985 Springer-Verlag.